Exporting and strengthening moderate Islam at the Muhammadiyah Australia College (MAC) - Syamsul Arifin; U. Umiarso (Universitas Muhammadiyah Malang, 2024)
The community service program aimed to promote moderate Islamic values within the academic community at Muhammadiyah Australia College (MAC). The program seeks to integrate these values into educational practices and establish MAC as an international agent of Indonesian moderate Islam. This initiative involves Focus Group Discussions (FGDs) and workshops, engaging stakeholders such as the Muhammadiyah Special Branch Leadership (PCIM) in Melbourne, MAC’s management and teaching staff, and the Muhammadiyah Central Leadership. The Universitas Muhammadiyah Malang (UMM) service team leads the activities with support from the Indonesian Ministry of Religion. Through collaborative efforts, this program works to identify community-driven solutions and develop a structured, community-based approach for strengthening moderate Islam in education. By leveraging the Indonesian Muslim diaspora's role, the program fosters inclusivity and social cohesion. This initiative reflects Muhammadiyah’s tradition of inclusiveness, creating synergy between institutions to enhance the resilience and reach of moderate Islam in diverse cultural and educational settings globally.